Meta Analysisi Of The Influence Of Media Learning Science On The Competency Of First School Student - Ira Yusna Sari; Yurnetti Yurnetti (Department of Science Education, 2022)
Science is a branch of science whose focus is on nature and the processes in it. Science deals with how to understand nature systematically. Science learning at the junior high school level in the 2013 curriculum is carried out in an integrated manner. The principle of cohesiveness is the study of living thing s and their relationship to physics and chemistry. In science learning, sometimes there are phenomena that are difficult to observe, hear, touch and feel directly, so that students sometimes experience difficulties because science is a science that requires an understanding of the material to be given. One way to solve this problem is by presenting learning media that makes learning clear, interesting, and easy to understand so that it can improve student learning competencies.The method used in this research is descriptive followed by meta-analysis. The research population was articles with the problem of the influence of integrated science learning media on junior high school students' competencies published in ISSN journals both nationally and internationally. The research sample was 15 articles with similar problems.The articles analyzed revealed that overall the research conducted had an effect and was effective on the Cognitive Competencies of junior high school students. This can be seen from the analysis of research results in the literature and supported by the average effect size. The use of Science Learning Media has an effect on class VII with an effect size (1.335) in the very high category, and student learning outcomes in the cognitive competency aspect (0.69) in the moderate category.